Ultrasonic assisted cross-flow ultrafiltration of starch and cellulose nanocrystals suspensions: Characterization at multi-scales. (25th June 2015) - Jin, Y.; Hengl, N.; Baup, S.; Pignon, F.; Gondrexon, N.; Sztucki, M.; Romdhane, A.; Guillet, A.; Aurousseau, M.
Highlights: Concentration profiles and structural organizations during cross-flow ultrafiltration by in-situ SAXS. Rheological behavior on SNC suspensions. Enhancement of filtration performance of SNC and CNC suspensions with ultrasound. Abstract: This study investigates for the first time the behaviors of starch and cellulose nanocrystals (SNC and CNC) suspensions which are simultaneously subjected to pressure, shear flow and ultrasound (US) during cross-flow ultrafiltration. This multi-forces process was characterized from macro-scales to nano-scales, with a custom designed "SAXS Cross-Flow US-coupled Filtration Cell". In addition, rheological behaviors of SNC samples at different concentrations/temperatures have been investigated. In both cases (ultrafiltration of SNC and CNC suspensions), better performances were observed with US. The in-situ SAXS measurements revealed that for SNC suspensions, no structure change occurred at the length scales range from 10 to 60 nm in this multi-forces process, while CNC particles exhibited an ordered arrangement within the concentrated layer during the same process. SNC particles accumulated on the membrane surface forming a "fragile" concentrated layer which was removed very quickly by subsequent applied US. In contrary, the CNC particles accumulation was very severe, the additional ultrasonic force led to a disruption but not a totally removal of the CNC concentrated layer.